Development of immunotherapy for high-grade gliomas: Overcoming the immunosuppressive tumor microenvironment - Franson, Andrea; McClellan, Brandon L.; Varela, Maria Luisa; Comba, Andrea; Syed, Mohammad Faisal; Banerjee, Kaushik; Zhu, Ziwen; Gonzalez, Nazareno; Candolfi, Marianela; Lowenstein, Pedro; Castro, Maria Graciela (Frontiers in Medicine, 2022)
The preclinical and clinical development of novel immunotherapies for the treatment of central nervous system (CNS) tumors is advancing at a rapid pace. High-grade gliomas (HGG) are aggressive tumors with poor prognoses in both adult and pediatric patients, and innovative and effective therapies are greatly needed. The use of cytotoxic chemotherapies has marginally improved survival in some HGG patient populations. Although several challenges exist for the successful development of immunotherapies for CNS tumors, recent insights into the genetic alterations that define the pathogenesis of HGG and their direct effects on the tumor microenvironment (TME) may allow for a more refined and targeted therapeutic approach. This review will focus on the TME in HGG, the genetic drivers frequently found in these tumors and their effect on the TME, the development of immunotherapy for HGG, and the practical challenges in clinical trials employing immunotherapy for HGG. Herein, we will discuss broadly the TME and immunotherapy development in HGG, with a specific focus on glioblastoma multiforme (GBM) as well as additional discussion in the context of the pediatric HGG diagnoses of diffuse midline glioma (DMG) and diffuse hemispheric glioma (DHG).